2016
DOI: 10.1182/blood-2015-10-672766
|View full text |Cite|
|
Sign up to set email alerts
|

Role of platelets, neutrophils, and factor XII in spontaneous venous thrombosis in mice

Abstract: Key Points• Platelets, neutrophils, and coagulation factor XII are implicated as important players in experimental venous thrombosis pathophysiology.• We demonstrate that platelets, but not neutrophils, are critical in spontaneous venous thrombosis, whereas low factor XII aggravates thrombosis.Recently, platelets, neutrophils, and factor XII (FXII) have been implicated as important players in the pathophysiology of venous thrombosis. Their role became evident in mouse models in which surgical handling was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…A TF-dependent coagulant state promotes fibrin formation in large vessels in DVT (see 150). Despite much evidence that neutrophils play important roles in venous thrombosis, the role of platelets and FXII has been recently emphasized (151). Neutrophils kill and remove bacteria and viruses at sites of infection and the NETs consisting of scaffolds of histone-containing chromatin fibers, serine proteases and released reactive oxygen species allow this to be done on a large scale.…”
Section: Net Formationmentioning
confidence: 99%
“…A TF-dependent coagulant state promotes fibrin formation in large vessels in DVT (see 150). Despite much evidence that neutrophils play important roles in venous thrombosis, the role of platelets and FXII has been recently emphasized (151). Neutrophils kill and remove bacteria and viruses at sites of infection and the NETs consisting of scaffolds of histone-containing chromatin fibers, serine proteases and released reactive oxygen species allow this to be done on a large scale.…”
Section: Net Formationmentioning
confidence: 99%
“…A model of spontaneous venous thrombosis in mice was developed using siRNA-mediated reductions of the coagulation regulatory proteins antithrombin and protein C [126]. When an siRNA that reduces FXII was studied in this model, surprisingly, there was an acceleration of thrombosis [127]. This suggests that FXII may serve a previously unrecognized regulatory (antithrombotic) function.…”
Section: Therapeutic Targeting Of Contact Factorsmentioning
confidence: 99%
“…22,103 In contrast, a model of spontaneous venous thrombosis using small interfering RNA knockdown of protein C and antithrombin, showed that although neutrophils were associated with venous thrombi, neutrophil depletion did not diminish thrombus formation. 104 Interestingly, protein arginine deiminase 4 (PAD4) and neutrophil elastase, which regulate chromatin decondensation and NETosis, have contradictory influence on DVT induction. Although PAD4 deficiency was associated with impaired thrombus formation in the IVC stenosis model, 105 an electrolytic injury model reported no influence of PAD4 deficiency on DVT.…”
mentioning
confidence: 99%